دور المرشد النفسي في تعديل العادات الدراسية الخاطئة من وجهة نظر الطلبة "دراسة ميدانية على عينة من طلاب الصف الثالث الثانوي في مدينة طرطوس" - ناصر عائشة; عباس سوسن (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف البحث الحالي إلى دراسة دور المرشد النفسي في تعديل العادات الدراسية الخاطئة من وجهة نظر طلبة الصف الثالث الثانوي وفق استبانة تتضمن أربعة أبعاد: تحديد أهداف المراجعة, تحديد مكان المراجعة, تحديد أوقات المراجعة, تحديد طرق المراجعة, كما يهدف إلى دراسة الفروق بين الطلاب في رأيهم بدور المرشد النفسي في تعديل العادات الدراسية الخاطئة تبعاً لمتغيري الجنس والاختصاص. اعتمد الباحث المنهج الوصفي, وتمّ تطوير استبانة وتوزيعها على عينة بلغت (300) طالباً وطالبة من طلاب الصف الثالث الثانوي في مدينة طرطوس, وأعيد منها (291) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (97%). وباستخدام الأساليب الإحصائية المناسبة كان من أهم نتائج البحث: إنّ دور المرشد النفسي في تعديل العادات الدراسية الخاطئة لدى طلبة الصف الثالث الثانوي العلمي هو دور جيد بالنسبة لجميع أبعاد الاستبانة, وبأهمية نسبية بلغت (75.3%) للبعد الأول المتمثل بتحديد أهداف المراجعة, و(77.38%) للبعد الثاني المتمثل بتحديد مكان المراجعة, و(76.94%) للبعد الثالث المتمثل بتحديد أوقات المراجعة, و(75.16%) للبعد الرابع المتمثل بتحديد طرق المراجعة, و(76.26%) لجميع الأبعاد. كما أظهرت النتائج عدم وجود فروق دالة إحصائياً بين متوسط درجات الطلاب في دور المرشد النفسي في تعديل العادات الدراسية الخاطئة تبعاً لمتغيري المؤهل العلمي والاختصاص, وذلك على الأبعاد الفرعية والمقياس ككل. The current research aims to examine the role of counselor to modify habits tuition wrong from the standpoint of third grade students of secondary according to a questionnaire includes four dimensions: determining audit objectives, identifying revision place, determine the review times, determine the review methods, also aims to study the differences among students in their view the role of counselor to modify the wrong habits of study depending on the variables of sex and jurisdiction. Researcher descriptive approach was adopted, has been developed to identify and distribute a sample of (300) students from third grade secondary students in the city of Tartous, and was re-ones (291) to identify a full and valid for statistical analysis, and response rate (97%). And using appropriate statistical methods was the most important results: The role of counselor to modify habits tuition wrong with the third grade secondary science students is a good role for all resolution dimensions, and the relative importance of (75.3%) for the first post of determining audit objectives, and (77.38 )% for the second goal after determining revision place, and (76.94%) for the third goal after determining Times review, and (75.16%) for the fourth goal after determining review methods, and (76.26%) of all dimensions. The results also showed no statistically significant differences between the average scores of students in the role of counselor to modify the wrong habits of study depending on the qualification and competence of variables, and that the sub-dimensions and scale as a whole.